Patterns of variation influencing antipsychotic treatment outcomes in South African first-episode schizophrenia patients. (February 2014) - Drogemöller, Britt I; Niehaus, Dana JH; Chiliza, Bonginkosi; Merwe, Lize van der; Asmal, Laila; Malhotra, Anil K; Wright, Galen EB; Emsley, Robin; Warnich, Louise
Aim: Many antipsychotic pharmacogenetics studies have been performed examining candidate genes or known variation; however, our understanding of the genetic factors involved in antipsychotic pharmacogenetic traits remains limited.Materials & methods: A well-characterized cohort of first-episode schizophrenia (FES) patients was used to identify a subset of nonresponders and responders to antipsychotic treatment for exome sequencing (n = 11). The variation observed in the responders and nonresponders was subsequently compared and a prioritization strategy was employed to identify variants for genotyping in the entire FES cohort (n = 103) as well as an additional Xhosa schizophrenia cohort (n = 222).Results: Examination of coding variation revealed a potential role for rare loss-of-function variants in treatment response outcomes. One variant, rs11368509, was found to be weakly associated with better treatment outcomes in the FES cohort (p = 0.057) and the Xhosa schizophrenia cohort (p = 0.016). In addition, the majority of the loss-of-function variation that was considered likely to be involved in antipsychotic treatment response was either novel or rare in Asian and European populations.Conclusion: This pilot study has highlighted the importance of exome sequencing for antipsychotic pharmacogenomics studies, particularly in African individuals. Furthermore, the results emphasize once again the complexity of antipsychotic pharmacogenomics and the need for future research. Original submitted 8 July 2013; Revision submitted 24 October 2013